Enhancing Learning Outcomes Through Educational Games in Islamic Cultural History at MI Roudlatul Huda Bibrik Jiwan Madiun - Masrukin A. (Nexus Publishing NXP, 2025)
This classroom action research (CAR) aimed to enhance learning outcomes in Islamic Cultural History for fourth-grade students at MI Roudlatul Huda Bibrik Jiwan Madiun through the integration of educational games. Employing a cyclical CAR framework, the study was conducted in two cycles, each comprising four stages: planning, implementation, observation, and reflection. Educational games were strategically incorporated to foster student engagement, motivation, and active participation in lessons. Data were gathered through pre-tests, post-tests, classroom observations, and reflective journals to assess the impact of the intervention. Findings demonstrated a marked improvement in students’ comprehension, retention, and overall academic performance, as evidenced by increased test scores and active classroom involvement. The interactive nature of educational games not only made learning more enjoyable but also facilitated deeper understanding of historical concepts. Furthermore, students exhibited enhanced problem-solving skills, collaboration, and enthusiasm towards the subject. The study underscores the effectiveness of game-based learning in transforming traditional pedagogical approaches, making Islamic education more dynamic and student-centered. These findings provide significant insights for educators aiming to revitalize religious studies by incorporating interactive and student-centered learning strategies that cater to diverse learning preferences. The research highlights how game-based learning can bridge the gap between traditional didactic methods and contemporary pedagogical approaches, fostering a more engaging and cognitively stimulating environment. By showcasing the tangible benefits of educational games in enhancing comprehension, retention, and student motivation, this study contributes to the broader discourse on modernizing instructional techniques to elevate the overall quality and effectiveness of Islamic education.